Анатомия узлов солнечного сплетения и их связей у белки обыкновенной (Sciurus vulgaris L.) - Лобко, П.И. (Вестник зоологии, 1972)
The structure of solar plexus in Sciurus vulgaris L. was studied.
It was established
that the plexus more often consists of four nervous nodes (two splanchnic, cranial me-senteric and left suprarenal). The nodes are connected by nervous ligaments, which may be divided into two groups. Homolateral ligaments, connecting the nodes of right and left sides between themselves belong to one group and transversal ligaments or comissu-res, connecting the nodes of the right side with the similar nodes of the left part of the plexus belong to the second group. An assymetry is observed in formation and structure of great splanchnic nerves. The right great splanchnic nerve is formed by one - five stalks deviating from the sympathetic stem of the right side at the level of the 9th thoracic vertebra - Ist lumbar vertebra. The left nerve is formed by one - three stalks deviating from the sympathetic stem at the level of the 9th thoracic vertebra - 2d lumbar vertebra. The relations are established of the nodes of solar plexus with dorsal stem of vagus nerves.